The Relationship between Professional Competence and Productivity and its Impacts on Teachers’ Job Satisfaction at Junior High School Rawajitu Timur Lampung - Made Wahyu Sudrajad, I; Yusoff Mohd Nor, Mohamed; ., Karwono; Suliman, Ashairi; Ihsan Dacholfany, M; Norhaini Mansor, Azlin; Hanim A. Hamid, Aida; Dewi Setyowati, Ratna; ., Lismayanti (International Journal of Engineering and Technology, 2018)
Teachersâ€™ job satisfaction is an interesting and imperative issue for both teachers and educational institutions. Job satisfaction enhances the quality of teacher's life. As for the educational institutions, the stability of job satisfaction level will establish a balance between and smoothness of productivity and professional teachersâ€™ competence. This study identifies the relationship between professional competence and teachersâ€™ productivity and its impacts on teachersâ€™ job satisfaction. Using questionnaires as the research instrument, this quantitative study revolves around the context of Rawajitu Timur Lampung. For this study, 44 teachers from three different high schools were selected as the respondents. A descriptive analysis generated revealed high levels of professional competence, teachersâ€™ productivity, and teachersâ€™ job satisfaction. Using Pearson correlation, the result showed that there was a significant positive relationship between professional competence and teachersâ€™ productivity towards teachersâ€™ job satisfaction, respectively. In addition, multiple regression analysis revealed that the combination of professional competence and teachersâ€™ productivity increased teachersâ€™ job satisfaction. The finding demonstrated the area of teachersâ€™ job satisfaction and related factors to fathom greater the relationship between teachers' professional competence and productivity. Taking into account the results of the study, educational institutions may boost teachersâ€™ professional competence and productivity to nurture job satisfaction.Â Â Â